Ethnobotany of wild edible plants in Soro District of Hadiya Zone, southern Ethiopia - Mulatu Hankiso; Bikila Warkineh; Zemede Asfaw; Asfaw Debella (BMC, 2023)
Abstract Background Despite their paramount importance all over the globe in supporting food security, information about wild edible plants is generally patchy. In this study, we investigated the wild edible plants used by the local people in the Soro District of Hadiya Zone, southern Ethiopia. The main purpose of the study was to document and analyze the indigenous and local knowledge of the people on their abundance, diversity, use and management. Methods and materials Purposive sampling and systematic random sampling were used to identify informants who can give information about the wild edible plants of the area. Data were collected by interviewing 26 purposively sampled key informants and 128 systematically randomly sampled general informants using semi-structured interviews. Guided observations and 13 focus group discussions (FGDs) consisting of 5-12 participants/discussants at each FGD session were also undertaken. Statistical analyses (mainly descriptive statistics approaches) and common analytical tools of ethnobotany including informant consensus, informant consensus factor, preference ranking, direct matrix ranking, paired comparison and index of fidelity level were applied to the data sets. Results A total of 64 wild edible plant species belonging to 52 genera and 39 families were recorded. All of these species are indigenous, 16 are new additions to the database and seven of them, including Urtica simensis and Thymus schimperi, are endemic to Ethiopia. In about 82.81% of the species, the edible plant part is also used in the Ethiopian traditional herbal medicine. It is striking to see that almost all wild edible plants recorded from the study area are nutraceutical plant species, serving multiple roles as food and therapeutic sources for the local people. We recorded five growth habits of 34.38% trees, 32.81% herbs, 25% shrubs, 6.25% climbers, and 1.56% liana. We found the Flacourtiaceae, Solanaceae, and Moraceae to be families that represented more species (4 each), followed by Acanthaceae, Apocynaceae, Amaranthaceae, and Asteraceae, which accounted for 3 species each. Fruits (53.13%) and leaves (31.25%) were consumed in more proportions than other edible parts (15.63%); mostly the ripe, raw fruit is eaten upon simple processing, followed by leaves eaten after boiling, roasting and cooking. Conclusion The frequency and intensity of consumption of these plants varied significantly (P < 0.05) with gender differences, key and general informants, and people's religious backgrounds. We postulate that priority setting for in situ and ex situ conservation of multipurpose wild edible plants in human-inhabited landscapes is essential to warrant sustainable use and conservation of the species as well as the use of new modes of application and valorization.